Educational innovation in Spain from the point of view of participants - Marcelo García, Carlos; Mayor Ruíz, Cristina; Gallego Noche, Beatriz (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article is a summary of a broader research related to the analysis of educational innovation in Spain. In the paper we analyze data from 933 projects of educational innovation that responded to a questionnaire. The results describe the origins of innovation projects, its content, work processes, outcomes and difficulties in implementation and dissemination of educational innovations.